2019
DOI: 10.1021/acsomega.9b01504
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the E-Cigarette Emission Profile by the Ratio of Glycerol to Propylene Glycol in E-Liquid Composition

Abstract: The use of electronic cigarettes (E-cig) is popular because of the perception that they are less addictive and safer compared to the traditional cigarettes. Nevertheless, there are still harmful effects associated with chemicals emitted from E-cig. Identifying the sources of the emitted compounds can be challenging because of the differences in the design of E-cig devices and the variability in the composition of E-cig liquids used in these devices. In this study, the emission profiles from impurity-free E-liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 63 publications
2
49
0
Order By: Relevance
“…Bekki et al 51 attributed the formation of carbonyls and dicarbonyls in e-cigarette aerosols to the oxidation of the e-liquid, when it becomes in contact with the heated atomiser coil in the presence of atmospheric oxygen. The present study suggests that the compounds observed by Ooi et al 52 are formed in the e-liquid of our model system prior to vaping, in part or in the whole. The difficulty in quantifying the concentration of these adducts prevented a fuller assessment of the role of each phenol compounds in reducing carbonyl formation.…”
Section: Trapping Of Carbonyls and Formation Of Adductssupporting
confidence: 67%
“…Bekki et al 51 attributed the formation of carbonyls and dicarbonyls in e-cigarette aerosols to the oxidation of the e-liquid, when it becomes in contact with the heated atomiser coil in the presence of atmospheric oxygen. The present study suggests that the compounds observed by Ooi et al 52 are formed in the e-liquid of our model system prior to vaping, in part or in the whole. The difficulty in quantifying the concentration of these adducts prevented a fuller assessment of the role of each phenol compounds in reducing carbonyl formation.…”
Section: Trapping Of Carbonyls and Formation Of Adductssupporting
confidence: 67%
“…The solvents in e-liquid are typically a mixture of propylene glycol (PG) and vegetable glycerol (VG) at variable ratios. 10 Researchers have raised concern about the inhalation toxicity of these solvents alone, even without nicotine and flavoring chemicals. 35 When PG and VG are exposed to heat, breakdown products include three aldehydes: formaldehyde, acrolein, and acetaldehyde.…”
Section: E-liquid Solventsmentioning
confidence: 99%
“…53,55 Solvent mixtures on the current market span the range from 100% PG, to 50/50, to 100% VG. 10 Studies showed that e-liquids with a higher VG content produce more formaldehyde and acrolein than those with more PG, especially at high power settings. This might expose e-cigarette users to higher aldehyde levels than smokers 10,56,57,58 and is a concern for "cloud chasers," who prefer VG-heavy e-liquids for the large visible clouds they produce.…”
Section: E-liquid Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when e-liquids are heated, a number of harmful compounds—including formaldehyde, acetaldehyde, methylglyoxal, acrolein, acetone, benzaldehyde, and the so-called BTEX compounds (benzene, toluene, ethylbenzene, and xylenes)—are found in the inhaled vapor. These are produced primarily by the oxidation and thermal decomposition of the two main components of e-fluid, glycerol and PG [ 31 ]. Moreover, e-liquids contain a range of flavorings, such as fruit and sweet flavors sold under names such as “Candy Corn”, “Chocolate Fudge”, and “Berry Splash”; in 2014, and the number of e-liquid flavors exceeded 7500, and it continues to increase [ 32 , 33 ].…”
Section: E-cigarettesmentioning
confidence: 99%